Exploring the drivers, scope and perceived success of e-commerce strategies in the UK retail sector - Neil Doherty; Fiona Ellis-Chadwick (2009)
Purpose - The purpose of this study is to explore empirically the relationship between the scope of the e-commerce strategies currently being deployed by the largest and most influential UK-based retailers, the drivers for their adoption, and perhaps most importantly the degree to which they are perceived to be successful.Design/methodology/approach The objectives of this research were addressed by using a quantitative research strategy, based on a postal questionnaire survey of the UK's largest retailers. The research strategy produced a wealth of primary data, which were thoroughly analysed using a variety of multivariate, statistical techniques.Findings - The study's findings suggest that the scope of the retailers' e-commerce strategies is strongly associated with the strength of management support behind the strategy and its perceived strategic fit. By contrast, the perceived success of their strategies is most strongly associated with the degree to which the retailer has deployed a portfolio of appropriate resources and capabilities, in support of its online operations.Research limitations/implications - The major limitation associated with the study is with respect to the rather disappointing response rate of 10 per cent. However. this level of response is similar to many previous surveys in this domain, and it is probably not surprising, given the commercially sensitive nature of the data. Moreover, the extensive phone-based follow-tip of non-respondents has provided an important reassurance that any resultant bias is likely to have only a modest effect on the results.Practical implications - The findings highlight that, despite their close relationship, the scope of an e-commerce strategy and its success are rather different entities, and therefore the factors that affect the scope of adoption cannot be relied on to deliver success In particular, retailer managers must recognise that, while their support and commitment may well be the impetus necessary to deliver a wide-ranging strategy, its ultimate success may be dependent on their ability to deploy a suitable portfolio of resources and capabilitiesOriginality/value - The study makes a major contribution in a number of ways. It provides one of the first attempts to measure the relationship between the drivers, scope and perceived success of e-commerce strategies, and, in so doing, it delivers an objective comparison between those factors that affect the scope and the success of e-commerce strategies Moreover, important new measures of e-commerce scope and success have been developed and deployed.